Optimization Model of Tourist Transportation Route based on Multi-Neuron Algorithm - Xiong, Jiang (2022 IEEE 2nd International Conference on Electronic Technology, Communication and Information (ICETCI), 2022)
Tourismis an enjoyable consumption behavior. With the improvement of the economic level, tourism allows people to experience the joy of life and at the same time promotes the development of tourism. But people have to plan their itinerary before traveling, and people have to consider transportation, transportation routes, scenic spots and destinations. So how to plan a reasonable route to improve the tourist experience is the research direction of this article. Based on this, this article takes the route planning of a tourist attraction as an example. According to the known scenic spots and traffic conditions on the four routes, the route is comprehensively scored using the tourist traffic route optimization model based on the multi-neural algorithm. The research shows that the A route score is 3.76 points. The score of route B is 3.14 points, the score of route C is 4.59 points, and the score of route D is 4.28 points. Therefore, when tourists travel in this scenic spot, route C is the route with the best sight viewing and transportation convenience.